Operational modal analysis tests on peruvian historical buildings : the case study of the 19th century hotel comercio - Aguilar, R. (2012)
The paper presents the preliminary round of in-situ experimental tests carried out at the “Hotel Comercio”, a historical construction located at Lima´s Historical Centre. The building is a three story republican-type construction built at the 19th Century with a composite structure of adobe and “Quincha”. The experimental works consisted on modal identification tests aiming at identifying the dynamic characteristics of the building using the environmental noise as source of excitation. Outstanding results were obtained in terms of modal properties since the first two translational modes and subsequent seven local modes were properly identified. The results confirm the expected different behaviour of the quincha panels and the adobe in terms of flexibility. An important contribution of the paper is the introduction of these tests as a tool for better understanding the structural behaviour which may also allow assessing the real damage condition of the buildings, as well as the seismic resistance.